'Persistence of the social': The role of cognitive ability in mediating the effects of social origins on educational attainment in Britain. (December 2018) - Bourne, Mollie; Bukodi, Erzsébet; Betthäuser, Bastian; Goldthorpe, John H.
Highlights: Cognitive ability mediates under 50% of the effect of social origins on education. There has been no sustained increase or decrease in this figure over recent decades. The mediating role of cognitive ability changes little across the educational career. These findings hold regardless of how we measure social origins. Such inequalities are not primarily due to differences in cognitive ability. Abstract: In this paper, we address two research questions on the basis of the series of British birth cohort studies. First, how large is the part played by cognitive ability in mediating the association that exists between individuals' educational attainment and their social origins, and is there evidence of any change in the importance of its mediating role over recent decades? Second, does the importance of its mediating role change over the course of individuals' educational careers? As regards the first question, we find that only around half of the effects of individuals' social origins on their educational attainment is mediated via their cognitive ability, as measured in early life. There has been some fluctuation in the mediation percentage over time, but no sustained increase. Moreover, this is the case in whatever way we measure social origins. As regards the second question, we find that the mediating role of cognitive ability changes little in importance as individuals' educational careers progress, with the possible exception that it declines in the case of an educational threshold relating to upper secondary qualifications. In the light of our results, we call into question the idea that the intergenerational reproduction of educational inequalities is driven overwhelmingly via the intergeneration transmission of cognitive ability; and also claims such as those made by Marks (2014) of 'the decline of the social' in the determination of the educational attainment of children from more or less advantaged families. While the relative importance of different forms of parental resources for children's educational success may be changing somewhat, our findings indicate a strong 'persistence of the social'.